Research Topic Trends In Information And Communication Technology Indexed Science And Technology Index (Sinta) 1 Year 2021 With The Zipf Approach - Via; Nining Sudiar; Vita Amelia (Universitas Airlangga, 2023)
ABSTRACT This study aims to find out about the trend topics that are more often discussed in Information & Communication Technology journals indexed by SINTA 1 in 2021 so that they can bring up the latest research subjects. The method used in this research is to use the bibliometric data analysis method based on the zipf rule. The results showed that there was the word